Review of #FAKENEWS. Noua cursã a înarmãrii [#FAKENEWS. The new arms race] by Alina Bârgăoanu - Elena Negrea-Busuioc (Romanian Journal of Communications and Public Relations, 2019)
“Fake news is neither fake, nor news” – Alina Bârgăoanu bluntly states in her latest book focusing on the overhyped phenomena of fake news and disinformation. An awful lot of public discussion and publications, both academic and popular literature, have been generated, during the last five years or so, by the fake news mania worldwide. However, significantly fewer efforts have been made to dissect and clarify the nature and, more importantly, the political, social and even psychological implications of fake news and disinformation exponentially increased spread.